Between Scylla and Charybdis: religion, the military and support for democracy among Egyptians, 2011–2014. Issue 2 (17th February 2018) - Hassan, Mazen; Kendall, Elisabeth; Whitefield, Stephen
ABSTRACT: Democracy as a form of civilian rule must navigate a path between clerical and military powers, both of which are highly engaged in the politics of post-Mubarak Egypt. The authors ask in this article how mass support for democracy changed in Egypt between 2011 and 2014, and how this support is connected with views on religion and the role of the military. This question is important for understanding the prospects for democracy in a major state in the Arab world. It is also of comparative interest because of what change in the social and ideological drivers of mass attitudes may tell us about the nature of democratic support more generally. The authors' analysis is based on nationally representative surveys of Egyptians in 2011 after the country's first post-Mubarak parliamentary elections and in 2014 after the removal of the Islamist President Morsi. The findings indicate that Egyptians in large numbers favour both democracy and unfettered military intervention in politics. The authors also observe important shifts in the social bases of support for democracy away from religion but also from economic aspiration. Negative political experience with democratic procedures in 2011–2013 seems to be the strongest factor behind the observed decrease in democratic support.